Division of the Year Award - Mohanty, Bimal Prasanna (Journal of the Inland Fisheries Society of India, 2020)
Division of the year - 2018-19 awarded to FREM Division, ICAR-CIFRI Barrackpore. the Editor-in-Chief, JIFSI and Head of Division -FREM receiving the trophy from the Chief Guest on CIFRI Foundation Day (17 March 2019)